Distribución espacial de Ocypode quadrata (Decapoda: Ocypodidae) en ocho playas de la zona norte oriental de Cuba - Ocaña, Frank A. (2012)
Spatial distribution of Ocypode quadrata (Decapoda: Ocypodidae) in eight beaches of North- Eastern Cuba. Studies on the ecology of Ocypode quadrata have been mostly carried out in the Northern and Southern part of its distribution range. In despite that this species is common in Cuban beaches, there are no quantitative studies regarding its abundance and spatial distribution. The aim of this study was to report some aspects about the spatial variation of O. quadrata density in sandy beaches, with different levels of human influence, in the North coast of Eastern Cuba. For this, on May 2010, eight beaches with different levels of human influence were surveyed. On each beach, the number of crabs burrows were counted in 45 quadrats of 4m2 located in three different strata (P1, P2 and P3). According to burrow opening diameter, crabs were separated into young and adults forms. To determine the existence of statistical differences in the density of crab burrows among beaches and strata, a two-way ANOVA was developed with a Scheffé-procedure post hoc test. A total of 355 burrows were counted in 360 sample units. The composition by size classes was 237 burrows for young and 118 for adults. From the total of burrows, 74% were located in P1, 20% in P2 and 6% in P3. The higher concentration of burrows was found at Jiguaní beach (0.52±0.08 burrows/m2) while the lesser concentration was found at Estero Ciego beach (0.06±0.01 burrows/m2). Most of the beaches did not present significant differences in the burrows density (Scheffé, p>0.05), according to ANOVA results, in despite their different human influence level. Density of individuals was significantly higher in the upper intertidal (P1) areas (Scheffé, p<0.05) with predominance of young crabs. Total density diminished in P2 and P3 strata where a predominance of adult individuals was observed. The interaction term of beach and strata evidenced that the pattern of variation among strata was not the same for all beaches. The general pattern of adults and young specimen spatial distribution in the beaches was very similar to those reported in the literature. In the present study, the first conducted in Cuban beaches, we did not find evidence of direct relationship between the level of human impact and the density of ghost crab burrows.